Preparation of 3-benzyloxy-2-pyridinone functional linkers: tools for the synthesis of 3, 2-hydroxypyridinone (HOPO) and HOPO/hydroxamic acid chelators. Issue 49 (9th December 2015) - Gibson, Sarah; Fernando, Rasika; Jacobs, Hollie K.; Gopalan, Aravamudan S.
Abstract: In contrast to 2, 3-dihydroxypyridine, the 3-benzyloxy protected derivative, 2, undergoes facile alkylation at ambient temperatures with a variety of functionalized alkyl halides in good yields. This alkylation has been used to prepare a number of linkers that permit the attachment of 3, 2-HOPO moieties onto various scaffolds using a wide range of coupling methods. The Mitsunobu reaction of 2 with representative alcohols was found to be of limited value due to competing O-alkylation that led to product mixtures. The phthalimide 3j can be converted in two steps to HOPO isocyanate 6 in excellent yields. Isocyanate 6 can be coupled to amines at room temperature or to alcohols in refluxing dichloroethane to obtain the corresponding urea or carbamate linked ligand systems. The coupling of isocyanate 6 with TREN followed by deprotection gave the tris-HOPO 10, an interesting target as it has both cationic and anionic binding sites. The HOPO hydroxylamine linker 11 was shown to be especially valuable as its coupling with carboxylic acids proceeds with the concomitant generation of an additional hydroxamate ligand moiety in the framework. The utility of this linker was shown by the preparation of two mixed HOPO-hydroxamate chelators, 16 and 19, based on the structure of desferrioxamine, a well-known trihydroxamate siderophore. Graphical abstract: